Determinants of savings in Malaysia / Nuraisya Maisara Md Noor Aizuddin and Juliana Mohd Abdul Kadir - Md Noor Aizuddin, Nuraisya Maisara; Mohd Abdul Kadir, Juliana (UiTM Cawangan Johor, 2019)
This study evaluates the responses of economic determinants towards savings in Malaysia. This study uses four determinants of savings which are inflation, economic growth, age dependency ratio and money supply for the period of 31 years from 1986 to 2016. This study focuses only on Malaysia as the subject. All data were collected from the World Bank and Bank Negara Malaysia. Unit root test such as ADF and PP were used to determine the stationarity of data. Ordinary Least Square estimator of regression was applied to analyse the model. From the findings, it is discovered that inflation and economic growth give positive and significant impact on savings, while age dependency ratio and money supply has a negative and insignificant relationship towards savings.